2016
DOI: 10.1001/jamaoncol.2015.5536
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of Digital Breast Tomosynthesis Compared With Digital Mammography

Abstract: Digital breast tomosynthesis screening outcomes are sustainable, with significant recall reduction, increasing cancer cases per recalled patients, and a decline in interval cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(129 citation statements)
references
References 28 publications
7
115
2
2
Order By: Relevance
“…If the interval cancer rate remains unchanged then it could be argued that screening DBT is predominantly increasing overdiagnosis and is unlikely to impact on breast cancer mortality. A recent US study has shown a trend towards a lower interval cancer rate following the introduction of tomosynthesis screening (17).…”
Section: Tomosynthesis and Overdiagnosismentioning
confidence: 99%
“…If the interval cancer rate remains unchanged then it could be argued that screening DBT is predominantly increasing overdiagnosis and is unlikely to impact on breast cancer mortality. A recent US study has shown a trend towards a lower interval cancer rate following the introduction of tomosynthesis screening (17).…”
Section: Tomosynthesis and Overdiagnosismentioning
confidence: 99%
“…In one study [42], over a 3-year period DBT recall rates at the population level remained statistically significantly lower than those for digital mammography alone, with recall rates of 88, 90, and 92 cancers per 1000 women screened for the first 3 years of DBT, respectively, versus a recall rate of 104 recalls per 1000 women screened with FFDM alone. A nonsignificant trend of increasing cancer detection rate over time was noted, from 5.5 at the prevalence screening examination to 6.1 cancers per 1000 women in year 3 of DBT [42]. A prospective trial conducted within a European screening program [43] reported a significantly increased cancer detection rate for women screened with both FFDM and DBT compared with FFDM alone (6.3 vs 8.5 cancers per 1000 women, respectively).…”
Section: Synopsis and Synthesis Of Evidencementioning
confidence: 99%
“…This cautiousness is due to the need to avoid an increase in overdiagnosis and costs. First results for a reduction from 0.7 to 0.5 interval cancers per 100 screened women were recently reported from a large study in the US [29], but further evidence is needed.Note H. During a breast examination performed outside the screening setting, it is the choice of the radiologist whether to perform only mammography, to associate tomosynthesis and/or ultrasound, or also to perform tomosynthesis without standard mammography and to obtain reconstructed synthetic mammograms. This decision is based on various issues: the characteristics of the breast, the availability of previous examinations, the availability of technology and also the radiologist’s preference in relation to the specific case.…”
Section: New Mammographic Techniques: Tomosynthesis and Contrast-enhamentioning
confidence: 99%